Penyelenggaraan Kota Layak Anak di Kota Depok (Studi Penelitian di Kota Depok Tahun 2015) - Reviansyah Ramadhan; Turtiantoro . (Journal of Politic and Government Studies, 2017)
Abstract: Children have a very important role, because they are the assets of the nation for the future days. Children also participate in the making of nation's history once becoming the mirror of the way of life of our nation in the future. Therefore, it required the protection to ensure the rights of children, to create the condition of Indonesian children whose ready to continue the wheels of nation's development in the future.The Child Friendly City (Kota Layak Anak / KLA) policy comes as the government's effort to improve the child welfare through the protection to ensure children's rights. This research is a policy studies that analyzes the primary consideration in the making of the Child Friendly City policy as well as the effort that Depok City Government takes to realizing the Child Friendly City in 2015 by using qualitative descriptive research method. This research was conducted in Depok, West Java. With data collection technique through in-depth interviews and documents.In the making of Child Friendly City in Depok, researcher founds that policy surroundings factors influence the primary consideration in the making of the policy include the international policy of the Child Friendly City concept comes as the follow-up of UN's Convention on the Rights of the Child. Researcher also found the policy implementation variables that influence implementation performance towards Depok City Government efforts to realize Depok as the Child Friendly City in 2015. Especially in these findings of the research, the absence of standards and policy goals are clear and vague, giving rise to multiple interpretations between the implementor of policies and affect the performance of policy implementation. Recommendations from the researchers is to made the Regional Action Plan as the standards and objectives of the policy. And also specialized training activities related to the Child Friendly City should be done to boost the quality of human resources of implementors and society.